Efektivitas Sistem Monitoring Dan Evaluasi Dalam Pengawasan Hutan Oleh Instansi Kehutanan Daerah - Syafaat, Ikhsan Hilal; Anggara, Oktavianus Cahya; Firmansyah, Rizky (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2026)
Forest monitoring is a critical instrument for ensuring the sustainability of forest resources at the regional level. This study aims to evaluate the effectiveness of forest monitoring carried out by the Bojonegoro District Forestry Branch Office using a qualitative descriptive approach through field observations, in-depth interviews, and document analysis. The evaluation focuses on institutional aspects, operational techniques, community participation, and the implementation of monitoring and evaluation (Monev) as well as the Follow-Up Action Plan (RTT). The findings reveal that although monitoring activities are routinely conducted, their effectiveness remains limited due to structural constraints such as inadequate human resources, underutilization of technology, and suboptimal inter-agency coordination. Reporting systems are still manually operated and not yet integrated digitally, while community involvement in monitoring lacks a well-defined structure. Moreover, Monev and RTT programs have not been systematically implemented nor based on measurable performance indicators. The study recommends strengthening technology-based monitoring systems, reformulating annual evaluation policies, and enhancing the capacity of local institutions and community participation. A collaborative approach involving cross-sector stakeholders is expected to improve monitoring effectiveness and support sustainable forest governance in Bojonegoro District.